Toward a co-Creation framework for developing a green sports event brand: the case of the 2018 Zürich E Prix. Issue 2 (3rd April 2021) - Bjerke, Rune; Naess, Hans Erik
ABSTRACT: This paper addresses the 2018 Zürich E Prix as a sport event brand and the city of Zürich as a key co-creator. We applied a conceptual and exploratory approach in a service-dominant logic (SDL) and co-creation perspective. Next to analysing the motor sport event and relevant documents related to the world championship, we interviewed a key informant representing the organising committee, which acted as the main co-creator. First, this paper offers a new understanding of the development of green sports event brands where a city plays a significant role. For instance, green city policy making, networking strategy and collaboration with stakeholders, logistical innovation, green event leadership, flexible management, and green social norms are areas, where a city can contribute substantially. The findings, supported by existing theory, are summarised in a conceptual model consisting of the green event support system and the formation of the green sports event brand. Further, based on relevant cross-disciplinary theories, the motor sport event case, information about the FIA Formula E world championship, and findings related to the strategic role of Zürich, we propose a co-creation framework consisting of four steps: (1) the strategy and support system: (2) the sports event experience; (3) the green sports event brand development; and (4) the event evaluation. This suggested framework for a green sports event brand serves as a guideline for developing a green sports event brand in a city new to the sports event tourism literature.